Castleman’s disease: an entity forgotten in ENT - Ali, Mohamed Riyas; Wadhwa, Vikram; Meher, Ravi; Tomar, Reena; Singh, Karishma; Singh, Nivea (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Castleman’s disease (CD) usually presents as localized or systemic lymphadenopathy or as an extra nodal mass. The usual site of presentation are mediastinum, retroperitoneum, axilla and mesentery. Only 3 cases of CD have been reported in retro pharyngeal space. We report a case of 20 year old male patient with retropharyngeal mass. He presented with difficulty in swallowing, change in voice and respiratory distress. The mass was removed in-toto transorally after performing elective tracheostomy. The histopathological findings were consistent with hyaline vascular type of CD. He was decannulated after two day and postoperative period was uneventful. Postoperative CT imaging confirmed the complete excision of tumor and patient is on follow up, with no signs of recurrence. The presentation of tumour in the retropharyngeal space which is a rare site of occurrence add to the uniqueness of this case. Unicentric CD has an excellent prognosis and surgery is the management of choice. Its clinical features, histological subtypes, treatment modalities and prognosis are discussed.